2004
DOI: 10.1002/gepi.20020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prospective and retrospective methods for haplotype inference in case‐control studies

Abstract: We compare bias and power of three methods for haplotype inference on disease risk using unphased genotype data from a case-control study. We examine the prospective score test of Schaid et al., a novel modification of the prospective estimating equations of Zhao et al. and the retrospective likelihood of Epstein and Satten. We find that all three approaches are roughly comparable when the haplotype effect on disease odds follows a multiplicative model. However, for dominant and recessive models of haplotype e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
112
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(118 citation statements)
references
References 16 publications
6
112
0
Order By: Relevance
“…While the HWE assumption often holds, situations may arise where we would expect departure from HWE, such as when inbreeding occurs or when population stratification exists and is unaccounted for in analysis. In such situations, Satten and Epstein (2004) showed that departure from HWE in the target population can lead to incorrect inference on haplotype effects in retrospective approaches. To resolve this problem, we could model the departure from HWE by estimating a fixation index among the control participants, as described in Satten and Epstein [2004] and Lin and Zeng [2006].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the HWE assumption often holds, situations may arise where we would expect departure from HWE, such as when inbreeding occurs or when population stratification exists and is unaccounted for in analysis. In such situations, Satten and Epstein (2004) showed that departure from HWE in the target population can lead to incorrect inference on haplotype effects in retrospective approaches. To resolve this problem, we could model the departure from HWE by estimating a fixation index among the control participants, as described in Satten and Epstein [2004] and Lin and Zeng [2006].…”
Section: Discussionmentioning
confidence: 99%
“…In such situations, Satten and Epstein (2004) showed that departure from HWE in the target population can lead to incorrect inference on haplotype effects in retrospective approaches. To resolve this problem, we could model the departure from HWE by estimating a fixation index among the control participants, as described in Satten and Epstein [2004] and Lin and Zeng [2006]. Satten and Epstein [2004] showed that including a single fixation index in the haplotype distribution greatly diminished the bias even in simulated data where individual haplotype pairs had a different fixation index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hardy-Weinberg equilibrium was evaluated in each group using a w 2 test for heterogeneity. BCL-2 haplotypes were estimated from the marker genotypes by a maximum likelihood ratio (LR) method using the CHAPLIN software, 25 which provides a LR statistic for testing the null hypothesis that there is no difference in the distribution of BCL-2 haplotypes between cases and controls. Logistic regression models were used to estimate the odds ratio (OR) and 95% confidence interval (CI) for the association between prostate cancer risk and BCL-2 genotypes and haplotypes, adjusting for potential confounders (i.e., age at the time of diagnosis for case subjects and at the time of ascertainment for controls), using the homozygous wild-type genotype as the reference group.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of haplotype-based association methods have been developed in both unrelated subjects (case-control or population-based) or in families; some of the more commonly used methods are listed in Table 1 (19,22,25,27,37,38). For example, Schaid and colleagues developed a regression-based score test for haplotype association in unrelated subjects that allows for testing of both global haplotype association and individual haplotype association as implemented in the Haplo.Stats program (19).…”
Section: Genetic Association Analysis With Haplotypesmentioning
confidence: 99%